A study of relationship between organisational commitment, pay satisfaction and turnover intention among employees of UEM Sunrise Berhad / Iskandar Zulkarnaen Muhamad Amin and Norfiza Emilya Mohamed Feisal - Muhamad Amin, Iskandar Zulkarnaen; Mohamed Feisal, Norfiza Emilya (Faculty of Business and Management, 2016)
This study intends to investigate the roles of organizational commitment and pay satisfaction towards turnover intention. Four objectives have been determined in order to achieve the purpose of this study. First, to identify the levels of organizational commitment, pay satisfaction, and turnover intention among employees in UEM Sunrise Berhad. Second, to investigate the relationship between organizational commitment and turnover intention. Third, to investigate the relationship between pay satisfaction and turnover intention. Fourth, to investigate the factor that gives most influence on turnover intention in UEM Sunrise Berhad. The population of the study consists of 360 employees, whilst the sample consists of 196 respondents from five departments, namely; Human Resource and Operations, Finance, ICT, Procurement and Contracts, and Development. The data were collected by distributing 270 questionnaires, and 260 returned questionnaires were used in the study. To analyse the data, descriptive, correlation, and regression analyses were used. The results of the study showed that there were moderate levels of organizational commitment, and pay satisfaction; and a high level of turnover intention in the organization. From the correlation analysis conducted, the results revealed that there are significant but inverse relationships between organizational commitment and turnover intention; and pay satisfaction and turnover intention. Additionally, the result of analysis also showed that there were weak but definite relationships between organizational commitment and turnover intention; and pay satisfaction and turnover intention. Meanwhile, from regression analysis conducted, it was found that pay satisfaction gave more influence to turnover intention, than organizational commitment. Last but not least, from the Model Summary derived from the analysis, it showed that organizational commitment and turnover intention only influenced turnover intention by 11.8%, and another 88.2% xiii was influenced by other factors. In a nutshell, organizational commitment and pay satisfaction do give influence over turnover intention, but in a small scale.¬